3D Hexaporous carbon assembled from single-layer graphene as high performance supercapacitor - Yadav, Prasad; Banerjee, Abhik; Unni, Sreekuttan; Jog, Jyoti Prakash; Kurungot, Sreekumar; Ogale, Satishchandra (Chemsuschem, 2012)
Keywords: Electrochemistry; Energy storage; graphene; porous materials; Supercapacitors

Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium

1D alignment of PEDOT in a buckypaper for high-performance solid supercapacitors - Soni, Roby; Anothumakkool, Bihag; Kurungot, Sreekumar (Chemelectrochem, 2016)
A flexible solid-state supercapacitor is prepared from carbon nanotube (CNT)-based buckypaper after forming a thin layer of polyethylenedioxythiophene (PEDOT) on the surface of the CNTs in the paper. A highly conducting PEDOT phase is obtained by interfacial polymerization, in which polymerization is confined at the interface of two immiscible liquids. The hydrophilic interaction between the functionalized CNTs and the oxidizing agent (iron perchlorate, Fe(ClO4)(3)), which is located in the aqueous phase, and the restricted interaction of the oxidizing agent with the EDOT monomer in the organic layer at the immiscible interface play a vital role in establishing a uniform and aggregate-free growth pattern of PEDOT on CNT. By carefully optimizing the amount of polymer in the paper, an electrode with a sheet resistance of 3.4(-1) and equivalent series resistance of 0.95 can be prepared. A thin and flexible solid-state supercapacitor device with an overall thickness of 210m is made by using this paper as the electrodes and poly(vinyl alcohol)/lithium chloride as the gel electrolyte. The power density and energy density of the electrode are 9.94Wcm(-3) and 8.85mWhcm(-3), respectively. The device also delivers a high volumetric capacitance of 18Fcm(-3) and areal capacitance of 354mFcm(-2). The demonstrated strategy is scalable and hence the process can be conveniently applied to prepare large-area PEDOT-modified buckypapers in a short time.
Keywords: Carbon; Energy storage; nanotubes; polymerization; Supercapacitors

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors

Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors

Synthesis of graphene from activated carbon at liquid nitrogen temperature and its detailed structural analysis - Sharma, Preeti; Sharma, Geeta; Punia, Rajesh (Applied Physics A-Materials Science & Processing, 2021)
The present study deals with the synthesis of graphene using thermal quenching of pre-heated activated carbon (a-C) (1370 K for 3 h) at liquid nitrogen temperature and its detailed structural analysis using XRD, TEM, FTIR and Raman spectroscopy. The analysis of lattice parameters (L-a, L-c,L- and d) of constituent nanographitic domains using XRD shows restoration of graphene-like structure in the resultant product (a-CL). TEM image reveals porosity and partially crystallinity (from SAED) in a-C. While thin layers of graphene are observed in the TEM images of a-CL Deconvoluted Raman spectra have been used to investigate the evolution of crystalline behaviour of a-C with temperature in view of Ferrari and Robertson's three-stage model. The evolution of G peak and increase in I-D/I-G reveals restoration of crystallinity in a-CL. The development of the D peak indicates disordering of graphite but ordering of amorphous carbon. The reported method is technologically beneficial for graphene synthesis for large number of applications such as supercapacitors, H-2 storage, gas separation and purification.
Keywords: activated carbon; Amorphous carbon; graphene; H-2 storage applications; Raman spectroscopy; Supercapacitors

Template directed synthesis of boron carbon nitride nanotubes (BCN-NTs) and their evaluation for energy storage properties - Karbhal, Indrapal; Chaturvedi, Vikash; Yadav, Poonam; Patrike, Apurva; Shelke, Manjusha V. (Advanced Materials Interfaces, 2023)
A unique approach has been applied for the synthesis of 1D boron carbon nitride nanotubes (BCN-NTs) using MnO2 nanowires as templates. BCN-NTs have been evaluated in Na-ion batteries, Li-ion batteries, and supercapacitors as electrode material and exhibited excellent and stable electrochemical performance. BCN-NTs as an anode for Na-ion battery has been shown to be highly stable up to 3000 cycles with capacity retention of 95 mAh g(-1), at a high current density of 1 A g(-1). In the case of the Li-ion battery, these BCN-NTs show a specific capacity of 563 mAh g(-1) at a current density of 50 mA g(-1). Finally, when used as an electrode for a supercapacitor, BCN-NTs display a specific capacity of 221 F g(-1) at a current density of 3 A g(-1) and 168 F g(-1) even at a very high current density of 30 A g(-1) exemplifying the excellent rate performance. The multifunctionality and stable performance of BCN-NTs among various electrochemical energy storage systems highlight the robustness of the material and make it an excellent candidate for scalable production and commercialization.
Keywords: 1D-nanostructure; boron carbon nitride nanotubes (BCN-NTs); Co-doping; Li-ion battery; Na-ion battery; Supercapacitors

Strategic design of a single-source precursor for in situ generation and integration of adherent species on Ni3S4 entangled-nanosheets for energy storage applications - Singh, Rahul; Thakur, Rohit; Sahu, Umasharan; Sahoo, Ramesh Chandra; Prasad, Bhagavatula L. V.; Matte, H. S. S. Ramakrishna (ACS Applied Nano Materials, 2025)
Synthesizing transition-metal chalcogenides (TMC) via a single-source precursor (SSP) route has shown great potential due to better reproducibility and control over stoichiometry, phase, and morphology. While the SSP converts into TMC, surfactants or coordinating species are essential to ensure dispersibility for further solution-based processing protocols. These additional species are typically highly toxic, difficult to remove, and adversely affect device performance. Here, as a proof of concept, design-induced in situ stabilized Ni3S4 (DiSNi) protocol demonstrates that strategic SSP design and optimized reaction conditions can facilitate directed chemical reactivity, gradually generating adhering species, which seamlessly integrate onto the metal chalcogenides, aiding the formation of stable dispersions without utilizing additional stabilizers. The proposed mechanism is validated by detailed strategic experiments and analysis, like X-ray photoelectron spectroscopy (XPS), accelerated dispersion stability measurements, and postsynthesis base treatment, which confirm the presence of in situ generated diethylammonium ion (DEA+) as the adherent and corroborate its role in dispersibility. The obtained Ni3S4 entangled-nanosheets are utilized to fabricate additive-free symmetric supercapacitors with organic electrolyte for charge storage over an extended potential window of 2.8 V and an energy density of 12.44 mu W h cm-2 at a power density of 0.42 mW cm-2. The devised DiSNi protocol showcases the importance of the SSP design for achieving multifunctionality. It is anticipated to have a broader impact on the role of careful design of SSP, making it an ideal contender for synthesizing transition-metal chalcogenides.
Keywords: dispersion stability; energy storages devices; low-boiling point solvents; nickel sulfide dispersions; organic electrolyte; single-source precursor; Supercapacitors